(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Fructose consumption has tremendously increased due to increased consumption of sweeteners in beverages, and this has been suggested to increase caloric intake. Higher caloric intake had been linked with diverse health consequences such as obesity, diabetes and cardiovascular diseases. Garlic (Allium sativum) has also been reported to be protective against adverse dietary effects. We hypothesized that increased caloric intake via sweetened drinks can cause hemorheologic, haematopoietic, nutritional, and metabolic derangements and that raw garlic homogenate consumption can mitigate these adverse effects. Therefore, we investigated the effects of increased caloric intake via sweetened drink as well as examined the potentials of raw garlic homogenate (RGH) to ameliorate such effects in Wistar rats. Twenty male Wistar rats were randomly divided into four groups (n=5): Control, Fructose (F) given fructose sweetened drink (FSD), Allium Sativum (AS) given raw garlic homogenate (RGH) (250 mg/kg/day) and F+AS given FSD and RGH (250 mg/kg/day) for nine weeks. Energy intake, haematopoiesis, metabolic risk factors, hemorheologic variables, fluid intake, liver enzymes and serum proteins were significantly increased by increased caloric intake via FSD consumption, however, RGH mitigated these effects in treated rats as observed from comparison between groups F and F+AS rats. The findings of this study revealed the fact that sugar sweetened beverages can increase caloric intake tremendously, even in the face of significantly reduced food intake and that RGH can ameliorate the adverse effects induced by high caloric intake in Wistar rats.